(3GdebfY hGdaUjds - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s ((3EHQGgje Hf CjhH GdHdGSi s)
(3ChdgG (B:s
(3jHOC HHGH PcQ ef LeY GdbQBf s
(3BNQgG (B:s
(3jfJgi HHGH PcQ GddGe Cda s
(3GdfSNI HgG MhGTs
(3jdjg ChQGb ai cjajI Yed GdMHQ ddcJGHI Ke GdbUjOI GdQGFjI GdTGWHjI ai QSe GdbQBfs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
Keywords: (3GdbQGAGJ hGdJLhjOs